Peran Keluarga dalam Perawatan dan Pengelolaan Pasien Penyakit Paru Obstruktif Kronik (PPOK): Tinjauan Literatur - Syahrizal Syahrizal; Hendra Kurniawan; Angelie Nopfitrah Sungkar; Firda Marsalisya (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive chronic illness that requires long-term management and active family involvement. Functional limitations, recurrent exacerbations, and psychosocial impacts highlight the importance of family support in COPD care. This study aimed to analyze the role of family in the care and management of patients with COPD through a systematic literature review. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were carried out using PubMed, Scopus, ScienceDirect, and Google Scholar with keywords related to COPD, family support, caregivers, self-management, and palliative care. Ten articles that met the inclusion criteria were analyzed using descriptive and thematic approaches. The findings indicate that family support plays a crucial role in improving self-efficacy, self-management behaviors, treatment adherence, and quality of life among patients with COPD. Family involvement also contributes to care decision-making, prevention of exacerbations, and the effectiveness of palliative care. However, caregiving responsibilities may impose physical and emotional burdens on caregivers. Therefore, COPD management should adopt a family-centered approach through education, continuous support, and caregiver empowerment to achieve comprehensive and sustainable patient care outcomes.